2005
DOI: 10.1007/s00248-004-0119-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Seasonal Dynamics of Extracellular Enzyme Activities in the Sediments of a Large Lowland River

Abstract: We tested whether seasonal changes in the sources of organic substances for microbial metabolism were reflected changes in the activities of five extracellular enzymes in the eighth order lowland River Elbe, Germany. Leucine aminopeptidase showed the highest activities in the water column and the sediments, followed by phosphatase > beta-glucosidase > alpha-glucosidase > exo-1,4-beta-glucanase. Individual enzymes exhibited characteristic seasonal dynamics, as indicated by their relative contribution to cumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 51 publications
8
30
0
Order By: Relevance
“…Furthermore, temperature can evidently not account for the often-elevated potential activities in spring, autumn and, in one case (chitinase), in winter. This limited temperature response is consistent with data from surface water (Sinsabaugh and Follstad Shah, 2010), fine sediments (Wilczek et al, 2005) and biofilms (Jones and Lock, 1993) of lowland streams and rivers and suggests important, seasonally varying determinants of enzyme activities in addition to temperature. One such factor is light.…”
Section: Temporal Variability Of Potential Enzyme Activitiessupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, temperature can evidently not account for the often-elevated potential activities in spring, autumn and, in one case (chitinase), in winter. This limited temperature response is consistent with data from surface water (Sinsabaugh and Follstad Shah, 2010), fine sediments (Wilczek et al, 2005) and biofilms (Jones and Lock, 1993) of lowland streams and rivers and suggests important, seasonally varying determinants of enzyme activities in addition to temperature. One such factor is light.…”
Section: Temporal Variability Of Potential Enzyme Activitiessupporting
confidence: 85%
“…Microbial activities in these patches also vary over time in response to temporal variation of environmental conditions (Jones and Lock, 1993;Wilczek et al, 2005;Sinsabaugh and Follstad Shah, 2010), changes in water availability (Romaní et al, 2006a, b;Artigas et al, 2009) and varying interactions among diverse microbial groups (for example, bacteria and algae; Romaní et al, 2006a, b;Ylla et al, 2009;Pohlon et al, 2010). This creates a spatiotemporal template that provides scope for gradients in environmental conditions along hydrological flow paths from upland sites to stream channels and longitudinally in stream corridors (Larned et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Increased ester and endopeptidase activity characterized kryal sediments, whereas a-glucosidase, b-glucosidase, b-xylosidase, N-acetyl-glucosaminidase, leucine aminopeptidase and phosphatase were more expressed in krenal systems. The importance of these typical krenal enzymes has been described for lowland rivers in both the water column and sediments (Wilczek et al, 2005) and mirrors the importance of gathering carbon, nitrogen and phosphorous from different sources. For instance, krenal systems have high carbon input via cellulose, thus expressing Bet becomes important within krenal sediments to gather carbon from this non-limiting resource (Zah and Uehlinger, 2001).…”
Section: Different Habitat Different Strategymentioning
confidence: 79%
“…The rate-determining step for both aerobic and anaerobic microbial degradation of POM and production of DOM is the hydrolysis by extracellular enzymes (Wilczek et al, 2005). Higher POM reactivity induces the production and activity of bacterial hydrolytic enzymes (Boetius and Lochte, 1994;Wilczek et al, 2005), and hydrolysis proceeds under both oxic and anoxic conditions, although not necessarily always at the same rates (Hansen and Blackburn 1991;Kristensen and Holmer, 2001). In this regard, Thibodeau et al (2010) recently reported that OM remineralization rates along the LC are highest in the lower estuary and decrease eastwards.…”
Section: Doc and Don Fluxesmentioning
confidence: 99%